ASSESSING THE DYNAMIC RELATIONSHIP OF STOCK MARKET, INTERNATIONAL TRADE AND ECONOMIC GROWTH: EMPIRICAL EVIDENCE FROM WAVELET ANALYSIS - Soh, Ann Ni; Jong, Meng Chang; Puah, Chin Hong; Mohammad Affendy, Arip (GEA College – Faculty of Entrepreneurship, 2021)
This paper aims to identify the nexus of stock market, trade and economic growth in Thailand. The study used approximately two decades of monthly data from 2000 to 2019. By applying the continuous wavelet transform (CWT) wavelet-based approach, the time-frequency and lead-lag relationships among the variables can be captured. Empirical findings reveal significant coherencies among the variables in the medium and long run with a positive association. Evidence reveals that the Thailand stock market plays a prominent and leading role in international trade. This study offers interesting findings about the lead-lag relationship between the stock market and economic growth, while the significant positive relationships among these two variables are validated. The theoretical implications have been justified, as these relationships are significant. The results obtained are vital for policymakers in framing effective macroeconomic policies regarding the Thailand stock market.